Dominicus Who? Solving the Riddle Posed by a Splendid “Venetian” Portrait Dated 1512, at the State Hermitage Museum - Perini Folesani, Giovanna (Actual Problems of Theory and History of Art, 2017)
The splendid portrait in the State Hermitage Museum dated 1512, usually attributed to Domenico Capriolo (1494–1528), is, in fact, a riddle. The bronze medal painted on the window sill showing a crouching roebuck (capriolo in Italian) surrounded by the inscription “MDXII — Dominicus — A. XXV” is generally mistaken for a signature and referred to its painter, sometimes identified as the sitter as well, regardless of the fact that by 1512 the painter Domenico Capriolo from Treviso should have been 18, not 25. Besides, the sitter is clearly a gentleman, not an artist. This attribution is even less tenable on account of the style, quality, and iconography of the picture, when compared to Capriolo’s undistinguished documented paintings. Thus, the inscription must be referred solely to the sitter (the roebuck being part of his family coat-of-arms, or a personal emblem: e.g. roebucks and/or harts were emblems of some members of the Contarini family in Venice since the late 14th century) and provides an obvious clue to his identification. Also the headless and almost armless antique statue of a Venus pudica in the background, clearly in the sitter’s possession, might provide a useful hint, just like the view of a Quattrocento church at the end of an imposing arcade with Corinthian columns ostensibly alluding to the sitter’s patrician palace. The peculiar façade of the church points to a location within the Venetian dominion and so does the known provenance of the painting. In the 17th century it featured prominently in the famous Muselli collection in Verona as a work by Giorgione (d. 1510), and as such it was largely copied in Northern Italy up to1587 and possibly even later. This early attribution is also untenable, but at least it acknowledges the remarkable quality of the picture. The original pose struck by the sitter was immediately imitated by Titian and even Raphaelfor some of their male portraits painted in the years 1513–1520. Via them, it came to influence 17th–century French and Netherlandish portraiture, as is proven by Le Brun’s Self-portrait in the Uffizi, Florence (1683), and by Rembrandt’s Self-portrait (1640) at the National Gallery, London. On the other hand, its composition looks related to contemporary Central Italian portraits. If all this is correct, it points to the identification of a brilliant “Venetian” painter, well above the standards of Bartolomeo Veneto, Palma the elder, Marco Basaiti, GiovanniCariani, Bernardino Licinio (and also of Lombard painters like Altobello Melone or the Piazzas) etc. and yet not unaware of them all. Albeit conversant with Giorgione’s and Palma’s work, this painter is familiar with Florentine painting as well. The fact that the sitter wears the same jacket as the young guy portrayed at about the same time in Lombardy against the background of the Lake of Iseo in a picture now in Philadelphia, equally boasting a Verona provenance suggests that they both wear a family livery, corresponding to the one of the aristocratic Capriolo family from Brescia (unrelated to the painter of the same name from Treviso). Their original fiefdoms overlooked the aforesaid Lake and included the village of Capriolo (hence their family name). Thus, its painter may well be somebody, like the Brescian painter Savoldo, whose work in the 1510s is still untraced and undocumented and who spent a period of his early life in Florence. The fact that this portrait was made in the aftermath of the bloody Sack of Brescia (February 1512) may well account for the return of the painter home to check on his family and belongings, as many other Brescian expats did.